Monitoring of Teachers’ Emotional Sphere - Stasiuk, Maria I. (Psychological Prospects Journal, 2017)
In the article it is highlighted the issue of psychological monitoring of emotional conditions of a pedagogue. It is indicated that pedagogical activity is characterized by tension, great amount of stress-factors that is why monitoring of emotional conditions is a precondition of professional growth of the pedagogue and prevents the occurrence of occupational deformations. Psychological monitoring is examined as a complex organizational technology of fixation, analysis and generalization of information on emotional conditions of the pedagogue for identifying trends and regularities of his or her professonal and personal development. While planning the psychological monitoring of emotional conditions of the pedagogue it was carried out formulation of problems and tasks, search and testing of monitoring tools, organization of expert procedures with further analysis and preparation of recommendations. It is shown that thanks to cyclicity, promptness, predictability monitoring contributes to finding reserves of activation of personal potential, increasing activity efficiency, personal growth of the pedagogue in all the spheres of his or her life. The objectivity of the obtained data was ensured by the presence of feedback, psychological tools which allow monitoring and recording the results at control (initial and final) stages of monitoring, the possibility of checking and assessing the state of professional growth, its monitoring according to a collectively created model and predicting of further professional and personal development of the pedagogue. With the help of the complex of psycho-diagnostic methods it was revealed the peculiarities of emotional and motivational conditions of the examined, in particular, motivation to success achievement, expressing frustration, tension, resistance and exhaustion. Frustration and stress are observed as the root causes of pedagogues’ problems in the professional sphere: frustration is accompanied by disappointment, despair, anxiety, anger and negatively affects functioning of the organism, exhausts the nervous system. Stress is characterized by negative emotional experience, defensive reactions, nervous and psychological tension, etc. It is grounded the importance of monitoring and psychological correction of negative emotional conditions of the pedagogue as a precondition of his or her professional growth. With the help of the methods of mathematical statistics, in particular, angular transformation of Fisher (φ*), it is proved the effectiveness of the suggested system of psycho-correctional events at the initial and final stages of psychological monitoring of emotional conditions of the pedagogue. Key words: psychological monitoring, emotional sphere, emotional conditions, pedagogue, professional activity, frustration, stress.